Analisis Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan Pasien Pra-Operasi Apendiktomi di RSU Bhakti Asih - Saryono Sudirman; Dessi Juwita; Wasiran Wasiran; Dwi Retno Handayani; Riska Reviana (Pusat Riset dan Inovasi Nasional, 2024)
Appendectomy is a surgical procedure performed to cut the inflamed appendix tissue. The appendectomy procedure can cause anxiety for appendicitis patients before the operation. If the coping usually used is not able to control anxiety, it can have an impact on increasing vital signs and delaying the operation. The aim of this research is to determine the factors related to the anxiety level of pre-operative appendectomy patients in the operating room at RSU Bhakti Asih Tangerang in 2024. The research method is quantitative research with a cross- sectional approach. The research sample was 56 patients using purposive sampling technique. The instrument used in this research was the Amsterdam Preoperative Anxiety and Information Scale (APAIS) surgical anxiety questionnaire in the operating room at RSU Bhakti Asih, Tangerang City. The data were analyzed using the statistical tests used, namely the bivariate test, namely Chi-Square and the multivariate test, namely the Backward logistic regression method. The results of the research show that there are three independent variables on the dependent variable. It shows that there is one dominant variable which has p > 0.05, namely the nurse support variable which can be seen from the OR value of 0.016 times (p < 0.007; 95% CI 0.016-0.521) which means that respondents who support from nurses, the risk will be 16 times greater and can prevent the occurrence of anxiety levels Pre-Appendectomy in the Surgical Room at RSU Bhakti Asih Tangerang, Year 2024. Conclusion, there is a relationship between the analysis of factors related to the level of anxiety of pre-operative appendectomy patients in the operating room at RSU Bhakti Asih Tangerang.